Phytochemical constitution and pharmacological effects of Genipa americana L. (Rubiaceae): a review - S. P. B. Franco; J. A. Silva; I. C. Barreto; S. P. M. Costa; A. L T. F. Borges; T. G. Nascimento; J. C. Silva; A. F. Santos; L. A. Rolim; J. R. G. S. Almeida (Brazilian Journal of Biology)
Abstract Genipa americana L., popularly known as “jenipapo”, is a species easily found, especially in northeastern Brazil. It is remarkable for having iridoids in its composition. Popular for its blue pigment which has been used to manufacture paints and dyes. Furthermore, this plant is utilized for medicinal purposes in addressing a variety of illnesses. This review provide a comprehensive picture of the phytochemical and biological activities characteristics of Genipa americana L. deal with its ethnomedicinal use and botany based on literature reports. These researches pointed out a range of secondary metabolites with iridoids being the most prevalent and abundant. Until now, the biological tests have shown important pharmacological activities, especially the antioxidant, insecticide and antibacterial activities. Besides presenting itself in a very promising way in other areas such as food and cosmetics industry, it is also used in popular medicine to treat several diseases having this potential use disseminated in its various parts. Finally, for a better analysis and validation of its health benefits and properties, extensive research is needed, including clinical trials. The information gathered and approached in this paper might support the planning and discussion of future studies on the topic.